PHANGS-JWST first results: variations in PAH fraction as a function of ISM phase and metallicity - Chastenet, Jérémy; Sutter, Jessica; Sandstrom, Karin; Belfiore, Francesco; Egorov, Oleg; Larson, Kirsten L.; Leroy, Adam K.; Liu, Daizhong; Rosolowsky, Erik; Thilker, David A.; Watkins, Elizabeth J.; Williams, Thomas G.; et al. (The astrophysical journal. Part 2, Letters, 2023)
We present maps tracing the fraction of dust in the form of polycyclic aromatic hydrocarbons (PAHs) in IC 5332, NGC 628, NGC 1365, and NGC 7496 from JWST/MIRI observations. We trace the PAH fraction by combining the F770W (7.7 μm) and F1130W (11.3 μm) filters to track ionized and neutral PAH emission, respectively, and comparing the PAH emission to F2100W, which traces small, hot dust grains. We find the average R PAH = (F770W + F1130W)/F2100W values of 3.3, 4.7, 5.1, and 3.6 in IC 5332, NGC 628, NGC 1365, and NGC 7496, respectively. We find that H ii regions traced by MUSE Hα show a systematically low PAH fraction. The PAH fraction remains relatively constant across other galactic environments, with slight variations. We use CO+Hi +Hα to trace the interstellar gas phase and find that the PAH fraction decreases above a value of in all four galaxies. Radial profiles also show a decreasing PAH fraction with increasing radius, correlated with lower metallicity, in line with previous results showing a strong metallicity dependence to the PAH fraction. Our results suggest that the process of PAH destruction in ionized gas operates similarly across the four targets.